Determinación de flujos de dióxido de carbono y dinámica estacional en tres turberas amazónicas, Loreto-Perú, 2018-2019 - Boullosa Puscan, Noris Daniela (2022)
Carbon dioxide (CO2) fluxes and their seasonal dynamics have been determined in the three peat bogs studied: Buena Vista, Quistococha and San Jorge. The methodology used was of a basic type, with a quantitative approach and a correlational assessment. For its development, static gas chambers. The monthly average CO2 flux of the three peatlands was quantified, as well as the temperature and precipitation for the period from May 2018 to April 2019. The results of the CO2 flux showed that the San Jorge peatland (SJO-02) presented higher fluxes at 566,32 ?mol m?² s?¹ compared to the Quistococha (QUI-02) and Buena vista (BVA-02) peatlands with values of 465,10 ?mol m?² s?¹ and 461, 13 ?mol m?² s?¹ respectively. Likewise, it was determined that the average of the San Jorge bog (SJO-02) varies significantly with respect to the rest of bogs. The results of the correlation analysis using the Pearson statistical test showed, of the peat bogs studied, Buena Vista (BVA_02) has a higher degree of direct and positive association between temperature and CO2 flows, with a p value =.738 and precipitation and CO2 fluxes, with a p value =.636. According to the statistical data obtained, it is concluded that temperature and precipitation are variables that influence the seasonal dynamics of CO2 flows.